Preliminary Analysis of Students' Problem Solving Ability and Self-Efficacy in IPAS Subject at Community Learning Center (CLC) Sabah Malaysia: Kemampuan Pemecahan Masalah dan Efikasi Diri - Anisa Vita Vela; Novi Ratna Dewi; Sri Sukaesih (Postgraduate, University of Mataram, 2025)
This study aims to analyze the problem solving ability and self-efficacy of students. The results of the problem solving ability research found that students who reached the KKM limit amounted to 2 people. The highest percentage of analysis of students' problem solving ability is in the indicator of understanding the problem, namely 51.7%. The lowest percentage is in the indicator of implementing the plan which is 24.6%. In addition, it was found that the level of self-efficacy of students was in the high category with three self-efficacy variables, namely the level of difficulty of the problem (level), resilience in solving problems (strenght), and breadth (generality). After the analysis, it was found that the relationship between high student self-efficacy was not directly proportional to the problem-solving ability of elementary school students at CLC Kemajuan Insan Inanam. Therefore, a comprehensive approach is needed to overcome the difference between student self-efficacy and student problem solving ability. So as to encourage the development of students' academic potential and thinking skills.